Factores materno-perinatales asociados a ictericia neonatal dependiente de fototerapia en un Hospital III – Iquitos, enero-diciembre 2023 - Custodio Flores, Liz Vanessa (2024)
Objective: To determine the maternal-perinatal factors associated with phototherapy-dependent neonatal jaundice at a Level III Hospital in Iquitos, from January to December 2023. Method: This was an observational, analytical, case-control, cross-sectional, and retrospective study, with a sample of 206 neonates diagnosed with neonatal jaundice, of which 103 were cases (phototherapy-dependent) and 103 were controls (not phototherapy dependent), based on the review of medical records. Results: A prevalence of 39.3% of neonatal jaundice cases was observed in 2023. There was a statistically significant association between phototherapy-dependent jaundice and the following factors: prematurity (OR = 7.6, p < 0.01); sepsis (OR = 8.5, p < 0.01); polycythemia (OR = 3.8, p = 0.012); second trimester urinary tract infection (OR = 2.3, p = 0.02) and chronic maternal hypertension (p = 0.014). On the other hand, exclusive breastfeeding was identified as a protective factor (OR = 0.2, p < 0.01). Conclusions: Prematurity, neonatal sepsis, polycythemia, lack of exclusive breastfeeding and second-trimester urinary tract infection, were significant risk factors for the development of phototherapy-dependent neonatal jaundice.